Analisis Faktor-faktor yang Mempengaruhi Kinerja Karyawan di Perusahaan Manufaktur: Sebuah Literature Review - Hilma Harmen; Dina Sarah Syahreza; Rexsy Mardohot Sitanggang; Karolin Gabrela Sitanggang; Ninda Rohani Situmorang; Nadia Natalia Sinurat; Rahel Marito Tambunan; Nicko Fernando Rajagukguk (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research focuses on the identification and analysis of employee performance factors in the context of the manufacturing industry. Through a comprehensive literature review, the study explores different aspects of organizations and how they interact with employee performance. Factors such as leadership, communication, motivation, work environment, and professional development are analyzed to understand the effect of employee performance. The results of this study are expected to provide new insights for stakeholders in the manufacturing industry to understand and improve organizational culture and employee performance. The research also highlights the need for further research in this area to understand the complex dynamics between organizational culture and employee performance.